2021
DOI: 10.3390/biomedicines10010001
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Sites of Action of Temozolomide for Pharmacological and Clinical Studies in Glioblastoma

Abstract: Temozolomide (TMZ), together with bulk resection and focal radiotherapy, is currently a standard of care for glioblastoma. Absorption, distribution, metabolism, and excretion (ADME) parameters, together with the mode of action of TMZ, make its biochemical and biological action difficult to understand. Accurate understanding of the mode of action of TMZ and the monitoring of TMZ at its anatomical, cellular, and molecular sites of action (SOAs) would greatly benefit precision medicine and the development of nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…However, it should be noted that the effect of vitamin C on demethylation of histones may antagonize the anticancer effect of DNA-alkylating drugs, such as temozolomide. MGMT promoter methylation is the key mechanism of MGMT gene silencing and predicts a favorable outcome in patients with glioblastoma who are exposed to alkylating agent chemotherapy [95,96]. We found that M/A did not abolish or decrease the cytotoxic effect of temozolomide in isolated glioblastoma cells (Figure S4, see the Supporting Materials).…”
Section: Discussionmentioning
confidence: 84%
“…However, it should be noted that the effect of vitamin C on demethylation of histones may antagonize the anticancer effect of DNA-alkylating drugs, such as temozolomide. MGMT promoter methylation is the key mechanism of MGMT gene silencing and predicts a favorable outcome in patients with glioblastoma who are exposed to alkylating agent chemotherapy [95,96]. We found that M/A did not abolish or decrease the cytotoxic effect of temozolomide in isolated glioblastoma cells (Figure S4, see the Supporting Materials).…”
Section: Discussionmentioning
confidence: 84%
“…Mass spectrometric (MS) quantification of temozolomide (TMZ)-induced DNA modifications would represent an ideal pharmacodynamic approach to monitor TMZ action in precision oncology and drug development for glioblastoma (GBM) . Among DNA modifications triggered by TMZ, the methylation of 2′-deoxyguanosine (2dGO) at the O6 position is the known one mainly responsible for TMZ action .…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric (MS) quantification of temozolomide (TMZ)-induced DNA modifications would represent an ideal pharmacodynamic approach to monitor TMZ action in precision oncology and drug development for glioblastoma (GBM) . Among DNA modifications triggered by TMZ, the methylation of 2′-deoxyguanosine (2dGO) at the O6 position is the known one mainly responsible for TMZ action . O6-methyl-2′-deoxyguanosine (O6-m2dGO) can be repaired by the methylguanine methyl transferase (MGMT), which is unfunctional in a majority of GBM patients, especially in the presence of mutations of isocitrate dehydrogenase (IDH) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations